"Ears of the Lynx" Sign in a Marchiafava–Bignami patient: Structural Basis and Fiber‐Tracking DTI Contribution to the Understanding of this Imaging Abnormality. Issue 2 (6th December 2012) - Pacheco, Felipe Torres; Rego, Milena Morais; do Rego, Jose Iram Mendonça; da Rocha, Antonio J.
ABSTRACT The "ears of the lynx" sign was previously reported as a neuroimaging finding observed in patients with autosomal recessive hereditary spastic paraplegia in association with a thin corpus callosum (ARHSP–TCC). We report a patient with a chronic form of Marchiafava–Bignami disease (MBD) that presented with this imaging feature. Diffusion tensor imaging (DTI) and fiber‐tracking data support that this finding is a consequence of the structural derangement, which enlarges a preexisting border zone of the bundles of fibers from the corpus callosum (CC) genu to the forceps minor and anterior corona radiata. Therefore, we assume that despite their pathological differences, damage to the anterior portion of the CC is responsible for the imaging similarities between MBD and ARHSP–TCC.